Retinal toxicity to antimalarial drugs: chloroquine and hydroxychloroquine: a neurophysiologic study - Farrell DF (Dove Medical Press, 2012)
Donald F FarrellUniversity of Washington School of Medicine, Seattle, WA, USAAbstract: Over a 30-year period, 29 cases of antimalarial retinal toxicity were studied in a tertiary medical center. Three cases of chloroquine and 26 cases of hydroxychloroquine toxicity were studied. A number of these cases were studied before multifocal electroretinogram (mfERG) became available and show how insensitive the corneal full-field flash ERG is in diagnosing this condition. It became apparent that even mfERG failed to diagnose some early patients who either had an abnormal fundus examination or Humphrey’s automated perimetry (protocol 10-2). The age of the patient and the number of years of exposure to antimalarial drugs appears to be directly related to the development of this retinal disorder. All three of the “quantitative retinal tests” recommended in the “Guidelines” – mfERG, spectral domain optical coherence tomography (SD-OCT), and autofluorescence – fail to identify all of the cases of antimalarial retinal toxicity. mfERG is probably the most sensitive of the three tests, but no direct comparison has yet been accomplished. None of these “quantitative tests” appear to provide the “gold standard” necessary for detecting early hydroxychloroquine retinal toxicity.Keywords: chloroquine, hydroxychloroquine, multifocal electroretinogram (mfERG), spectral domain optical coherence tomography (SD-OCT), autofluorescence